Intranasal inoculation of IFN-λ resolves SARS-CoV-2 lung infection via the rapid reduction of viral burden and improvement of tissue damage - Shin, Haeun; Kim, Sujin; Jo, Ara; Won, Jina; Gil, Chan Hee; Yoon, So Yeon; Cha, Hyunkyung; Kim, Hyun Jik (Frontiers in Immunology, 2022)
The innate immune responses of upper airway could further our understanding toward antiviral strategies against SARS-CoV-2. We characterize the potential of interferon (IFN)-λ as an innate immune inducer for the rapid clearance of SARS-CoV-2 in the lung and the therapeutic efficacy of intranasal inoculation of IFN-λ to resolve acute lung infection. SARS-CoV-2-infected Syrian golden hamsters exhibited a significant decrease in body weight and high viral mRNA level at 3 days post-infection (dpi). Although viral replication was reduced completely from 7 dpi, the pathologic findings remained prominent until 14 dpi in the lung of hamsters. The transcription of IFN-λ was significantly induced in response to SARS-CoV-2 infection with the increase of IFN-stimulated genes. Intranasal inoculation of IFN-λ restricted SARS-CoV-2 replication in the lungs of infected completely from 3 dpi with markedly reduction of inflammatory cytokines. The transcriptional phenotypes were altered to the direction of damage repair and tissue remodeling in the lungs of SARS-CoV-2-infected hamsters following intranasal inoculation of IFN-λ, which improved SARS-CoV-2-caused lung damage. Collectively, our findings suggest that IFN-λ might be a potent innate immune inducer in the lung and intranasal inoculation of IFN-λ resolves SARS-CoV-2 infection with rapid viral clearance and improvement of lung damage.